PROSPECTIVE DIRECTIONS OF TRANSFORMATION OF HUMAN CAPITAL DEVELOPMENT IN THE DIGITAL ECONOMY (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In this article, the system of human capital development has its own socio-economic orientation. In addition to the sum of the participants and their interactions, the human capital development system includes the environment, certain integration mechanisms that develop the interaction of the participants, and the adaptation mechanism that serves as the basis for the system's stability and self-development.
Keywords: economic subjects, development of human capital, educational field, income dynamics, vocational training, professional skills.